Smoking Decreases Survival in Locally Advanced Cervical Cancer Treated With Radiation. (March 2018) - Mayadev, Jyoti; Lim, Jihoon; Durbin-Johnson, Blythe; Valicenti, Richard; Alvarez, Edwin
Abstract : Purpose: To study the prevalence and effect of smoking on cervical cancer recurrence and mortality in patients undergoing definitive treatment with radiation. Materials and Methods: Between July 2007 and September 2013, 96 locally advanced cervical cancer patients received definitive radiation or chemoradiation followed by brachytherapy. Smoking status was obtained from prospective intake questionnaires and quantified by pack-years. Pelvic control (PC), disease-free survival (DFS), and overall survival (OS) were analyzed by multivariable Cox proportional hazards models. Results: Smoking history included 51 (53.1%) nonsmokers, 45 active smokers, and former smokers: 20 (20.8%) with 1 to 20 pack-years and 25 (26%) with 21+ pack-years. With a median follow-up of 2 years on univariate analysis, the impact of 1 to 20 pack-years on PC, DFS, and OS relative to nonsmokers was hazard ratio (HR) 4.29 (95% confidence interval [CI], 1.36-14.1; P =0.014), 4.99 (95% CI, 1.21-22.4; P =0.027), and 4.77 (95% CI, 1.34-17.8; P =0.017), respectively. For patients with 21+ pack-years, the impact on PC, DFS, and OS was HR=6.13 (95% CI, 2.29-18.6; P <0.001), 7.24 (95% CI, 2.28-29.1; P =0.001), and 4.21 (95% CI, 1.26-15.4; P =0.02). On multivariate analysis, there remained a significant difference of 1 to 20 pack-years smoking history on OS relative to nonsmokers, HR=4.68 (95% CI, 1.02-29; P =0.047). For patients with 21+ pack-years smoking history, there continued to be a negative impact on PC and DFS, HR=5.66 (95% CI, 1.7-22.18; P =0.004) and HR=6.89 (95% CI, 1.54-42; P =0.011), respectively. Conclusions: Former and active tobacco smoking during radiation therapy for cervical cancer is associated with unfavorable PC, DFS, and OS outcomes. The increased number of smoking pack-years conferred a worse outcome effect in those treated with radiation.